Evaluation of productivity in the extraction of bentonite clay in the municipality of Boa Vista, state of Paraíba, Brazil (Research, Society and Development, 2020)
This article presents a methodology for determining the productivity indexes of the unit operations of open pit mining of Bentonite ore, in the country Boa Vista, Paraíba1 country. The objective of this work is to verify possible inadequate procedures that can be optimized in the operation of the Primavera mine, in the county of Boa Vista, Paraíba country. The unit operations analyzed were the loading and transport stages. In this work, the study of times and movements was carried out to define the optimal cycle of operations, the number of suitable trucks and the productivity rate of the excavator. The results shown in this article show that there is a great loss of time during the loading operation. The average productivity calculation is 18, that is, this is the optimal number of trucks that must work in consortium with the excavator. The company currently works with 21 trucks and there are constantly queues for loading. Three fewer trucks represents a severe, rather considerable decrease in transportation costs. In addition, to obtain optimization in the loading stage, the average productivity of the equipment needs to be 217.14 m³ / hour. Thus, it was possible to define corrective measures to be taken to optimize the Unit Operations process at Mina Primavera. A productivity projection of 1,737.12 m³ / day was calculated, considering an 8-hour workday. Taking into account that Bentonite has a density of 1.5 ton / m³, the average value of productivity can be expressed in 2,605.68 ton / day.